Combined autologous blood patch-immediate patient rollover does not reduce the pneumothorax or chest drain rate following CT-guided lung biopsy compared to immediate patient rollover alone. Issue 160 (March 2023) - Duignan, John A.; Ryan, David T.; O'Riordan, Brian; O'Brien, Amy; Healy, Gerard M.; O'Brien, Cormac; Butler, Marcus; Keane, Michael P.; McCarthy, Cormac; Murphy, David J.; Dodd, Jonathan D.
Highlights: Combined ABP-IPR did not reduce pneumothorax or chest drainage compared to IPR alone and may be a safer approach following CT-guided lung biopsy. Pneumothorax predictors adjusted for ABP-IPR and IPR alone included age, lesion size, location, patient position, emphysema, and lesion-pleura distance, Chest drainage predictors adjusted for ABP-IPR and IPR alone included lesion location, patient position, bullae crossed and lesion-pleura distance. Abstract: Puprose: The purpose of this study was to evaluate a combined autologous blood-patch (ABP)-immediate patient rollover (IPR) technique compared with the IPR technique alone on the incidence of pneumothorax and chest drainage following CT-guided lung biopsy. Methods: In this interventional cohort study of both prospectively and retrospectively acquired data, 652 patients underwent CT-guided lung biopsy. Patient demographics, lesion characteristics and technical biopsy variables including the combined ABP-IPR versus IPR alone were evaluated as predictors of pneumothorax and chest drain rates using regression analysis. Results: The combined ABP-IPR technique was performed in 259 (39.7 %) patients whilst 393 (60.3 %) underwent IPR alone. There was no significant difference in pneumothorax rate or chest drains required between the combined ABP-IPR vs IPR groups ( p =.08, p =.60 respectively). Predictors of pneumothorax adjusted for the combined ABP-IPR and IPR alone groups included age ( p =.02), lesion size ( p =.01), location ( p =.005), patient position ( p =.008), emphysema along the needle track ( p =.005) and lesion distance from the pleura ( p =.02). Adjusted predictors of chest drain insertion included lesion location ( p =.09), patient position ( p =.002), bullae crossed ( p =.02) and lesion distance from the pleura ( p =.02). Conclusion: The combined ABP-IPR technique does not reduce the pneumothorax or chest drain rate compared to the IPR technique alone. Utilising IPR without an ABP following CT-guided lung biopsy results in similar pneumothorax and chest drain rates while minimising the potential risk of systemic air embolism.